Brain Gym with Elderly Cognitive Function - Noyumala Noyumala; Musaidah Musaidah (Sarana Ilmu Indonesia (salnesia), 2023)
Memory is one of the cognitive processes that is usually worse in older people. Improving cognitive abilities can be done with brain exercises. This study aims to determine the effect of cognitive function on the elderly before and after brain training in the working area of ??the Bontoramba Public Health Center, Kab. Gowa, 2022. The type of research was a Pre-Experimental One Group Pretest-Posttest design using one group. A total of 35 subjects were selected using Purposive Sampling. Data collection was through interviews, while the MMSE (Mini Mental State Exam) instrument was used to measure the cognitive function of the elderly. Data analysis used the Wilcoxon test. The results showed that the analysis using the Wilcoxon test obtains Positive Ranks or difference (positive) values, which showed that there were 29 subjects whose cognitive function increased from the pre-test score to the post-test score, where the average increase score was 15,00 and the total score was 435,00. This means that there is a significant influence between the cognitive function of the elderly before and after the test. It is concluded that brain exercise has an effect on increasing the cognitive function of the elderly in the working area of the Bontoramba Health Center, Bontonompo District, Gowa Regency.